Business ethics : - Ghillyer, Andrew (McGraw Hill Higher Education, 2010)
This book provides assistance to employees by taking a journey through the challenging world of business ethics at the ground level of the organization rather than flying through the abstract concepts and philosophical arguments at the treetop level. By examining issues and scenarios that relate directly to their work environment (and their degree of autonomy in that environment), employees can develop a clearer sense of how their corporate code of ethics relates to operational decisions made on a daily basis.